ANALISIS EFEK VISKOSITAS TERHADAP TEGANGAN TEMBUS MINYAK TRANSFORMATOR - Admin APERTI (Aliansi Perguruan Tinggi Badan Usaha Milik Negara (APERTI BUMN), 2018)
In this research, high voltage testing on transformer oil were done to obtain its breakdown voltage. Type of the transformer oil that used in this testing is Shell Oil Diala B. The breakdown voltage test was carried out by increasing the temperature of the oil to change its viscousity. Half ball electrodes was used in the testing by applying AC high voltage 50 Hz to measure the breakdown voltage. Experimental results shows that the viscousity of the transformer oil is affecting the value of breakdown voltage. The breakdown voltage of the transformer oil will be bigger when the viscousity is lower. This is because oil which has low viscousity will be difficult to be contaminated by impurities that have potential to form conductive bridge on the oil.